High-thermal-conductivity nano coating, preparation method, secondary battery and electric device

By applying high-thermal nanocoating inside the secondary battery housing to form a thermal conductive layer, the problem of difficulty in heat management during fast charging and discharging of traditional secondary batteries is solved, and more effective battery cell heat release and performance improvement is achieved.

CN119859427APending Publication Date: 2025-04-22XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510109235.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

It is difficult for traditional secondary batteries to effectively manage the heat inside the battery cell during fast charging and discharging, resulting in an increase in the temperature of the battery cell center, affecting the performance and life.

Method used

High thermal conductivity nanocoatings are used, including a small layer of graphene powder, polycrystalline diamond powder, binding dispersant and solvent, to form a 50-100um thick thermal conductivity layer inside the shell to improve the thermal conductivity and heat dissipation effect of the battery cell.

Benefits of technology

Through the application of high thermal conductivity nanocoating, the center temperature of the battery cell is significantly reduced, the performance of the battery cell is optimized, the service life of the battery cell is extended, and the thermal management cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859427A_ABST
    Figure CN119859427A_ABST
Patent Text Reader

Abstract

The invention provides a high-thermal-conductivity nano coating, a preparation method, a secondary battery and an electric device, and the high-thermal-conductivity nano coating comprises the following components in percentage by mass: 5-20% of few-layer graphene powder; 15%-30% of polycrystalline diamond powder; the bonding dispersant is greater than 2%; and the balance of solvent. The thermal conductivity of the film formed by the high-thermal-conductivity nano coating is 1200-2500W / (m * K). The invention further provides a preparation method of the high-thermal-conductivity nano coating, and the preparation method has the characteristics of simple process and convenience in processing. The invention further provides the secondary battery and the power utilization device, the structure is simple, the heat conduction layer is formed by utilizing the high-heat-conduction nano coating, the problem that rapid heat production in the center of the battery cell is difficult to disperse in time is solved, heat dissipation of the battery cell is more uniform, and the cost of the secondary battery is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of secondary batteries, and in particular to a high thermal conductivity nano coating, a preparation method, a secondary battery and an electrical device. Background Art

[0002] At present, the market demand for fast charging capability of power batteries is getting higher and higher. In order to achieve rapid energy charging of secondary batteries in a short time, a very large current is required to charge the battery cell. In this process, full consideration should be given to the thermal management inside the battery cell. The traditional thermal management method is to perform air cooling or liquid cooling on the outside of the battery cell shell. However, due to the limitation of the thermal conductivity of the battery cell shell, the heat accumulation in the battery cell cannot be quickly discharged, which reduces the temperature of the center of the battery cell and reduces the performance and life of the battery cell. Summary of the invention

[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0004] On the one hand, the present application proposes a high thermal conductivity nano coating, wherein the thermal conductivity of the high thermal conductivity nano coating after film formation is 1200-2500 W / (m*K).

[0005] On the other hand, the present application proposes a method for preparing a high thermal conductivity nano coating, which has the characteristics of simple process and convenient processing.

[0006] On the other hand, the present application proposes a secondary battery, including a battery cell and a shell; wherein the interior of the shell is provided with a high thermal conductivity nano coating of the present application to form a thermal conductive layer with a thickness of 50-100um, which can enable the heat rapidly accumulated in the center of the battery cell to be evacuated in time and the heat dissipation of the battery cell to be more uniform, thereby reducing the overall cost of the battery cell package.

[0007] The last aspect of the present application proposes an electrical device, in which a secondary battery assembly with a thermal conductive layer with a thickness of 50-100um formed by the high thermal conductive nano-coating of the present application is arranged inside the shell and applied to the electrical device to improve the comprehensive performance of the electrical device and reduce the difficulty of thermal management of the electrical device.

[0008] According to the embodiment of the first aspect of the present application, a high thermal conductivity nano coating is proposed. Based on the high thermal conductivity nano coating as a benchmark, the coating includes 5%-20% of few-layer graphene powder; 15%-30% of polycrystalline diamond powder; greater than 2% of a bonding dispersant; and the balance is a solvent.

[0009] In some embodiments, the few-layer graphene powder has 3-10 layers.

[0010] In some embodiments, the bonding dispersant includes at least one of an amine compound, an alcohol compound, an acrylate compound, a polyester compound, or a pyrrolidone compound.

[0011] In some embodiments, the adhesive dispersant is polyvinyl pyrrolidone powder.

[0012] In some embodiments, the solvent is N-methylpyrrolidone.

[0013] In some embodiments, the viscosity of the high thermal conductive nano coating is in the range of 500-5000 mPa.s; its particle size is in the range of 10-30 um; and the thermal conductivity of the high thermal conductive nano coating after film formation is 1200-2500 W / (m*K).

[0014] According to an embodiment of the second aspect of the present application, a method for preparing a high thermal conductive nano coating is provided, comprising the following steps:

[0015] The few-layer graphene powder and the binding dispersant are dispersed by ball milling at a speed of 15-25 rpm for at least 30 minutes to obtain a first mixed material;

[0016] Adding the solvent to the first mixed material, and stirring and dispersing the mixture by ball milling at a rotation speed of 31-41 rpm for at least 1 hour to obtain a second mixed material;

[0017] The polycrystalline diamond powder is added to the second mixed material, and the mixture is dispersed by ball milling at a rotation speed of 31-41 rpm for at least 2 hours to obtain the high thermal conductive nano coating described in any of the above embodiments.

[0018] According to an embodiment of the third aspect of the present application, a secondary battery is provided, comprising a battery cell and a shell for accommodating the battery cell; wherein a thermal conductive layer with a thickness of 50-100 um formed by using the high thermal conductive nano coating described in any of the above embodiments is arranged inside the shell.

[0019] In some embodiments, the process of forming the thermal conductive layer includes: spraying the high thermal conductive nano coating described in any of the above embodiments on the inside of the shell to form a coating with a thickness of 50-100 um;

[0020] The shell is placed at 90-150° C. and baked for 10-30 minutes to volatilize the solvent in the high thermal conductive nano coating and form a uniform thermal conductive layer.

[0021] According to an embodiment of the fourth aspect of the present application, an electrical device is provided, which includes the secondary battery described in any of the above embodiments.

[0022] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0024] Figure 1 It is a flow chart of a method for preparing a high thermal conductive nano coating provided in one embodiment of the present application. DETAILED DESCRIPTION

[0025] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the present application includes all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.

[0026] This application is improved based on the defects of the following related technologies. With the vigorous development of the current new energy market, the market demand for fast charging capabilities of power batteries is getting higher and higher. From the initial 1-1.5C fast charging to the 2-3C fast charging batteries currently prevalent in the market. Different from the 0.5P charging rate requirement of traditional energy storage cells, on-board fast charging batteries must use very large currents to charge the cells because they require rapid energy charging in a short time. In this process, on the one hand, a large amount of heat will be generated due to the ohmic impedance and polarization impedance that must be overcome by the rapid deintercalation of lithium ions between the positive and negative electrodes inside the cell. On the other hand, the ohmic heat generated by the structural parts, especially the joints, will also become very huge, which makes it necessary to fully consider the thermal management inside the cell in the process of developing fast charging cells.

[0027] The traditional thermal management method is to use air cooling or liquid cooling on the outside of the battery cell shell. This solution can indeed reduce the heat generated inside the battery cell, but this method is limited by the thermal conductivity of the shell. At present, the thermal conductivity of iron is 80W / (m*k), the thermal conductivity of aluminum is 204W / (m*k), and the thermal conductivity of graphene is 3000-5000W / (m*k). Therefore, if excellent thermal conductive materials such as graphene can be used in the thermal management system of the battery cell, the performance of the entire battery cell will be greatly improved.

[0028] Based on this, the technical solution of the embodiment of the present application provides a high thermal conductivity nano coating, a preparation method, a secondary battery and an electrical device. The high thermal conductivity nano coating includes a few-layer graphene powder, a polycrystalline diamond powder, a bonding dispersant and a solvent. Through the scientific and reasonable proportion of each component, a viscosity range of 500-5000mPa.s and a high thermal conductivity nano coating with a particle size range of 10-30um are obtained; wherein the thermal conductivity of the high thermal conductivity nano coating after film formation is 1200-2500W / (m*K). By applying the high thermal conductivity nano coating to the secondary battery, a 50-100um thick thermal conductive layer is formed on the inner wall of the secondary battery shell, which can greatly optimize the release effect of the accumulated heat of the battery cell during the rapid charge and discharge process, thereby reducing the center temperature of the battery cell, optimizing the performance of the battery cell, and improving the long-term service life of the battery cell.

[0029] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0030] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0031] To achieve the above-mentioned purpose, according to the embodiment of the first aspect of the present application, a high thermal conductivity nano coating is proposed, which includes 5%-20% of few-layer graphene powder, 15%-30% of polycrystalline diamond powder, more than 2% of bonding dispersant, and the balance is solvent, based on the mass percentage content of the high thermal conductivity nano coating.

[0032] Among them, the high thermal conductivity nano coating includes a few-layer graphene powder, a polycrystalline diamond powder, a bonding dispersant and a solvent; wherein the high thermal conductivity nano coating is used as a benchmark, and the few-layer graphene powder is 5%-20% according to the mass percentage, wherein the number of layers of the few-layer graphene powder is 3-10 layers, wherein the thermal conductivity of graphene decreases with the increase in the number of layers, but single-layer graphene is difficult to prepare and expensive, so in this embodiment, considering the practical application and thermal conductivity, 3-10 layers of few-layer graphene powder are selected as the main thermal conductive material, and its thermal conductivity is 3000-5000W / (m*k). Compared with the main shell aluminum of the square battery cell in the related art (thermal conductivity is 204W / (m*k)), the high thermal conductivity nano coating in this application has an absolute advantage in thermal conductivity.

[0033] In some embodiments, the mass percentage of the few-layer graphene powder is 5%, 7%, 8%, 9%, 10%, 12%, 13%, 15%, 16%, 17%, 18%, 20%, etc., wherein if the content of the few-layer graphene powder is too much, such as greater than 20%, it cannot be dispersed normally, but will affect the thermal conductivity. Conversely, if the content of the few-layer graphene powder is too little, such as less than 5%, the generated high thermal conductivity nano coating cannot achieve suitable thermal conductivity.

[0034] In some embodiments, in this implementation, polycrystalline diamond powder is the main coating molding material, which provides structural strength for the high thermal conductivity nano coating after film forming, greatly improves the wear resistance and hardness of the high thermal conductivity nano coating after film forming, and extends the service life of the film; at the same time, polycrystalline diamond powder (thermal conductivity is 1642W / (m*k)) itself is also a high thermal conductivity material, and can also be used in combination with few-layer graphene powder to play an auxiliary role in thermal conductivity.

[0035] The mass percentage of polycrystalline diamond powder is 15%, 16%, 20%, 21%, 22%, 25%, 26%, 27%, 28%, 29%, 30%, etc. If the content of polycrystalline diamond powder is too much, such as greater than 30%, it will increase the cost of the high thermal conductivity nano coating and reduce the overall thermal conductivity of the film-forming coating of the high thermal conductivity nano coating; on the contrary, if the content of polycrystalline diamond powder is too little, such as less than 15%, the film-forming strength of the generated high thermal conductivity nano coating is insufficient and it is easy to fall off.

[0036] In some embodiments, the bonding dispersant includes at least one of an amine compound, an alcohol compound, an acrylate compound, a polyester compound or a pyrrolidone compound; wherein the amine compound and the alcohol compound are both small molecule compounds, and exemplary bonding dispersants include amine salts, quaternary ammonium salts, pyridinium salts, polyoxyethylene alcohol and polyvinyl pyrrolidone, etc. For example, in this embodiment, the high thermal conductive nano coating needs to be immersed in the electrolyte for a long time, and the bonding dispersants of amine compounds and alcohol compounds may have a risk of dissolution, but the acrylate compound, polyester compound or pyrrolidone compound are all suitable for the electrolyte environment for a long time. In some embodiments, the bonding dispersant is polyvinyl pyrrolidone to ensure that the secondary battery has absolute stability in long-term use.

[0037] Among them, the mass percentage of the bonding dispersant is greater than 2%, which is used for the few-layer graphene powder and polycrystalline diamond powder to be evenly and stably dispersed in the solvent system to form a nano-coating with a certain viscosity; for example, the mass percentage of the bonding dispersant is 3%, 5%, 7%, 8%, 9%, 10%, etc. If the mass percentage of the bonding dispersant is too small, the normal bonding effect cannot be achieved.

[0038] In some embodiments, the solvent is N-methylpyrrolidone (NMP). First, NMP, as the current mainstream solvent for positive electrode slurry, has good compatibility with the battery cell, has high solubility in various components in the high thermal conductivity nano coating, and is relatively cheap; secondly, even if some of the solvent NMP remains, it will not affect the performance of the battery cell. In some embodiments, based on the high thermal conductivity nano coating, the high thermal conductivity nano coating includes 10% of few-layer graphene powder, 20% of polycrystalline diamond powder, 5% of bonding dispersant, and 65% of N-methylpyrrolidone according to the mass percentage.

[0039] The viscosity of the high thermal conductive nano coating in the present application is in the range of 500-5000 mPa.s; its particle size is in the range of 10-30 um; and the thermal conductivity of the high thermal conductive nano coating after film formation is 1200-2500 W / (m*K).

[0040] According to the embodiment of the second aspect of the present application, a method for preparing a high thermal conductive nano coating is proposed, such as Figure 1 As shown, the following steps are included:

[0041] S1: mixing the few-layer graphene powder and the binding dispersant in proportion by ball milling and stirring at a speed of 15-25 rpm for at least 30 minutes to obtain a first mixed material;

[0042] S2: adding the solvent to the first mixture, and stirring and dispersing the mixture by ball milling at a rotation speed of 31-41 rpm for at least 1 hour to obtain a second mixture;

[0043] S3: adding polycrystalline diamond powder to the second mixed material, and stirring and dispersing by ball milling at a rotation speed of 31-41 rpm for at least 2 hours to obtain the high thermal conductive nano coating in any of the above embodiments.

[0044] Among them, in S1, the few-layer graphene powder and the bonding dispersant are added to the high-speed ball mill in proportion for stirring and dispersing, the stirring time is at least 30 minutes, and the rotation speed is 15-25rpm. For example, in this step, the rotation speed of the high-speed ball mill is 18rpm, 20rpm, 21rpm, 23rpm, 25rpm, etc.; the stirring and dispersing time is 30min, 32min, 33min, 35min, etc.; the few-layer graphene powder needs to be fully dispersed with the bonding dispersant powder to achieve a better dispersion effect. In this step, the rotation speed and dispersion time of the high-speed ball mill are limited to fully disperse the few-layer graphene powder and the bonding dispersant powder.

[0045] Wherein, in S2, all the solvents are added into a high-speed ball mill and mixed with the first mixed material, and the second mixed material is obtained by ball milling and stirring and dispersing at a rotation speed of 31-41rpm for at least 1h. Wherein in this step, the rotation speed of the high-speed ball mill is 31rpm, 36rpm, 38rpm, 39rpm, 41rpm, etc., and the stirring and dispersing time is 1h, 1.5h, etc. Among them, the most difficult to disperse in the high thermal conductive nano coating is the few-layer graphene powder. If the few-layer graphene powder is directly dispersed with the solvent without being dispersed by a bonding dispersant, the dispersion degree of the few-layer graphene powder will be affected.

[0046] In S3, polycrystalline diamond powder is added into a high-speed ball mill and mixed with the second mixed material, and the high thermal conductive nano coating in any of the above embodiments is obtained by ball milling and stirring at a speed of 31-41rpm for at least 2h. In this step, the speed of the high-speed ball mill is 31rpm, 36rpm, 38rpm, 39rpm, 41rpm, etc., and the stirring and dispersing time is 2h, 2.5h, etc. The ball milling and stirring of the polycrystalline diamond powder will generate a large amount of heat, and the bonding dispersant will affect its bonding and dispersing effect when stirred at high temperature for a long time. Therefore, after the few-layer graphene powder and the bonding dispersant powder are completely dispersed, they are stirred and dispersed with the solvent, and finally the polycrystalline diamond powder is added.

[0047] According to an embodiment of the third aspect of the present application, a secondary battery is proposed, comprising a battery cell and a shell for accommodating the battery cell; wherein a thermal conductive layer with a thickness of 50-100 um formed by using the high thermal conductive nano coating in any of the above embodiments is arranged inside the shell.

[0048] The secondary battery includes a battery cell and a shell for accommodating the battery cell, and the shell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and as plastic, polypropylene, polybutylene terephthalate, etc. may be listed. The present application has no particular restrictions on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0049] The shell in this embodiment is provided with a thermal conductive layer with a thickness of 50-100um formed by the high thermal conductive nano-coating in any of the above embodiments, wherein the thickness of the thermal conductive layer is 50um, 60um, 70um, 80um, 90um, 100um, etc. If the thickness of the thermal conductive layer is too large, it will have two effects. On the one hand, if the thickness is too large, it will affect the internal space of the battery cell. This application improves the thermal management under the premise of not affecting the internal design of the battery cell as much as possible, but it will also lead to increased costs. On the other hand, if the thickness of the thermal conductive layer is too large, it will also affect heat transfer and thus reduce thermal conductivity.

[0050] In some embodiments, the process of forming the thermal conductive layer includes: spraying the high thermal conductive nano coating in any of the above embodiments on the inside of the shell to form a coating with a thickness of 50-100um; baking the shell at 90-150°C for 10-30min to evaporate the solvent in the high thermal conductive nano coating and form a uniform thermal conductive layer.

[0051] The secondary battery in this application is conducive to the heat diffusion after the heat is generated inside the battery cell (especially the fast charging cell), reducing the temperature difference inside the battery cell, greatly reducing the additional thermal management cost, and at the same time helping to improve the long-term service life of the battery cell; it solves the problem of heat dissipation difficulty in the middle of the battery cell in the related technology, and can significantly improve the problem of slow heat dissipation of the lithium-ion battery structure itself, reducing the difficulty of battery thermal management from the design perspective. In addition, this application saves the overall cost of heat dissipation of secondary batteries, and the heat dissipation of the battery cell is faster and more uniform, and the structure is simple, the feasibility is high, and the impact on the internal design of the battery cell is small.

[0052] According to an embodiment of the fourth aspect of the present application, an electrical device is provided, which includes the secondary battery in any of the above embodiments.

[0053] To facilitate further understanding of the present application, the scheme of the present application is further described below in conjunction with the embodiments. Those skilled in the art will understand that the description in the present application is only part of the examples, and any other suitable specific examples are within the scope of the present application.

[0054] Example 1

[0055] The present embodiment provides a high thermal conductive nano coating, and its preparation method and specific operating parameters are as follows: based on the high thermal conductive nano coating as a benchmark, it includes 10% of few-layer graphene powder; 20% of polycrystalline diamond powder; 5% of polyvinyl pyrrolidone powder; and 65% of N-methyl pyrrolidone in terms of mass percentage.

[0056] Graphene and PVP powder are added into a high-speed ball mill according to the calculated mass ratio, stirred and dispersed, the stirring time is 30 minutes, and the speed is 20rpm to obtain a first mixture; then all N-methylpyrrolidone is added into the high-speed ball mill and mixed with the first mixture, stirred and dispersed for 1 hour, and the speed is 36rpm to obtain a second mixture; finally, polycrystalline diamond powder is added into the high-speed ball mill and stirred and dispersed with the second mixture for 2 hours, and the speed is 36rpm to obtain a high thermal conductive nano coating with a viscosity of 500-5000mPa.s; its particle size is 10-30um.

[0057] Example 2

[0058] Compared with Example 1, this embodiment has the following differences: the few-layer graphene powder is 5%; the polycrystalline diamond powder is 30%; the polyvinyl pyrrolidone powder is 5%; and the N-methyl pyrrolidone is 60%.

[0059] Example 3

[0060] Compared with Example 1, this embodiment has the following differences: the few-layer graphene powder is 20%; the polycrystalline diamond powder is 15%; the polyvinyl pyrrolidone powder is 5%; and the N-methyl pyrrolidone is 60%.

[0061] Comparative Example 1

[0062] Compared with Example 1, this comparative example has the following differences: the few-layer graphene powder is 2%; the polycrystalline diamond powder is 35%; the polyvinyl pyrrolidone powder is 5%; and the N-methyl pyrrolidone is 58%.

[0063] Comparative Example 2

[0064] Compared with Example 1, this comparative example has the following differences: the few-layer graphene powder is 25%; the polycrystalline diamond powder is 20%; the polyvinyl pyrrolidone powder is 5%; and the N-methyl pyrrolidone is 50%.

[0065] Test Case

[0066] The high thermal conductivity nano coatings in Examples 1-4 and Comparative Examples 1-2 were applied to secondary batteries, and the high thermal conductivity nano coatings in Example 1 were sprayed to the inside of the shell of the same specifications to form a 50um thermal conductive layer, a 60um thermal conductive layer, a 70um thermal conductive layer, an 80um thermal conductive layer, a 90um thermal conductive layer, a 100um thermal conductive layer, a 20um thermal conductive layer, a 150um thermal conductive layer, and a 200um thermal conductive layer, respectively, to obtain the first sample, the second sample, the third sample, the fourth sample, the fifth sample, the sixth sample, the second comparative sample, the third comparative sample, and the fourth comparative sample. The high thermal conductivity nano coatings in Example 2, Example 3, Comparative Examples 1 and Comparative Examples 2 were sprayed to form a 80um thermal conductive layer inside the shell of the same specifications, to obtain the seventh sample, the eighth sample, the fifth comparative sample, and the sixth comparative sample. Finally, a battery with an ordinary shell and no thermal conductive layer was used as the first comparison sample, in which all samples were assembled with the same winding core to ensure that all structures and materials except the thermal conductive layer in the shell were exactly the same. A temperature sensing wire was buried in the center of each group of batteries to detect the temperature changes of the core package during the charging and discharging process. After all samples were assembled, the cells were normally offline after the baking-liquid injection-formation-aging-capacity division process. The cells were cycled for three weeks under the high-rate charging conditions of 25℃4C SC / 1C. The temperature changes of the temperature sensing wire during the third week of charging were detected using the temperature sensing wire buried in the center of the core package. The results are shown in Table 1.

[0067] Table 1 Temperature changes of the temperature sensing line of different samples during the third week of charging

[0068]

[0069] According to the test results in Table 1, the charging temperature at the center of the battery cell of the fourth sample and the first comparative sample under the same conditions shows that the highest temperature at the center of the battery cell during charging in the first comparative sample without adding a thermal conductive layer reaches 54.3°C, and the maximum charging temperature rise reaches 24.7°C, while the highest temperature at the center of the battery cell in the fourth sample using a high thermal conductive nano coating is reduced to 46.9°C, and the maximum charging temperature rise is only 16.9°C. The highest temperature dropped by 7.4°C and the temperature rise dropped by 7.8°C. The experiment shows that the reasonable use of the high thermal conductive nano coating on lithium-ion batteries can significantly increase the thermal conductivity of the battery cell, thereby reducing the temperature at the center of the battery cell.

[0070] By comparing the fourth sample, the seventh sample, the eighth sample, the fifth comparative sample, and the sixth comparative sample, it can be seen that when the content of the few-layer graphene in the formula increases, the temperature rise at the center of the battery cell decreases first and then increases under the same charging conditions. When the content of the few-layer graphene is 10%, the minimum temperature rise inside the battery cell is 16.9°C. When the content of the few-layer graphene in the high thermal conductivity nano coating is 5-20%, the temperature rise at the center of the battery cell is less than 20°C during charging, and the maximum temperature of the battery cell is lower than 50°C, which is very beneficial for the thermal management and long-term use of fast-charging batteries.

[0071] When the graphene content in the fifth comparison sample was 2%, the temperature rise at the center of the battery cell reached 21.6°C, which was significantly higher. This may be due to the fact that the content of few-layer graphene in the formula was too little, resulting in the inability to effectively discharge the heat inside the battery cell. When the graphene content in the sixth comparison sample was 25%, the temperature rise at the center of the battery cell also reached 20.4°C. This may be due to the fact that the content of few-layer graphene was too much, resulting in its inability to disperse well. After the thermal conductive layer was dried, there was a phenomenon of graphene stacking, which led to an increase in the heat diffusion path and thus reduced the overall thermal conduction efficiency. According to the experimental results, the optimal ratio range of few-layer graphene in high thermal conductive nano-coatings is between 5% and 20%.

[0072] By comparing the first sample to the sixth sample and the second comparative sample to the fourth comparative sample, it is found that as the thickness of the thermal conductive layer increases, the temperature rise at the center of the battery cell under the same charging conditions first decreases and then increases. When the thickness of the thermal conductive layer is 80um, the minimum temperature rise inside the battery cell is 16.9℃. When the thickness of the thermal conductive layer is 50-100um, the temperature rise at the center of the battery cell during charging is less than 20℃, and the maximum temperature of the battery cell is lower than 50℃, which is very beneficial for the thermal management and long-term use of fast-charging batteries. When the thickness of the thermal conductive layer is 20um, the temperature rise at the center of the battery cell reaches 22.3℃, which is obviously higher. This may be due to the fact that the thermal conductive layer is too thin and the amount of thermal conductive material graphene is insufficient, resulting in the inability to effectively discharge the heat inside the battery cell. When the thickness of the thermal conductive layer exceeds 100um, such as 150um and 200um, the temperature at the center of the battery cell is also significantly higher than that of the thermal conductive layer thickness of 100um. This may be due to the "quilt effect" caused by the too thick thermal conductive layer, which causes the heat dissipation path in the thermal conductive layer to be too long, but reduces the overall thermal conductivity effect.

[0073] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0074] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A high thermal conductivity nano coating, characterized in that: Based on the high thermal conductive nano coating, the coating comprises 5%-20% of few-layer graphene powder, 15%-30% of polycrystalline diamond powder, more than 2% of bonding dispersant, and the balance of solvent according to the mass percentage.

2. The high thermal conductivity nano coating according to claim 1, characterized in that: The number of layers of the few-layer graphene powder is 3-10 layers.

3. The high thermal conductivity nano coating according to claim 1, characterized in that: The bonding dispersant includes at least one of an amine compound, an alcohol compound, an acrylate compound, a polyester compound or a pyrrolidone compound.

4. The high thermal conductive nano coating according to claim 3, characterized in that: The bonding dispersant is polyvinyl pyrrolidone powder.

5. The high thermal conductivity nano coating according to claim 1, characterized in that: The solvent is N-methylpyrrolidone.

6. The high thermal conductivity nano coating according to any one of claims 1 to 5, characterized in that: The viscosity of the high thermal conductivity nano coating is in the range of 500-5000 mPa.s; the particle size is in the range of 10-30 um; and the thermal conductivity of the high thermal conductivity nano coating after film formation is 1200-2500 W / (m*K).

7. A method for preparing a high thermal conductive nano coating, characterized in that: The following steps are involved: The few-layer graphene powder and the binding dispersant are dispersed by ball milling at a speed of 15-25 rpm for at least 30 minutes to obtain a first mixed material; Adding the solvent to the first mixed material, and stirring and dispersing the mixture by ball milling at a rotation speed of 31-41 rpm for at least 1 hour to obtain a second mixed material; Add polycrystalline diamond powder to the second mixed material, and stir and disperse by ball milling at a rotation speed of 31-41 rpm for at least 2 hours to obtain the high thermal conductive nano coating according to any one of claims 1-6.

8. A secondary battery, characterized in that: It comprises a battery core and a shell for accommodating the battery core; wherein the inside of the shell is provided with a thermal conductive layer with a thickness of 50-100 um formed by using the high thermal conductive nano coating described in any one of claims 1-6.

9. The secondary battery according to claim 8, characterized in that: The forming process of the heat conducting layer comprises: The high thermal conductivity nano coating described in any one of claims 1 to 6 is sprayed inside the shell to form a coating with a thickness of 50-100 um; The shell is placed at 90-150° C. and baked for 10-30 minutes to volatilize the solvent in the high thermal conductive nano coating and form a uniform thermal conductive layer.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.